2011
DOI: 10.1002/ajh.22115
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide and prednisone induction followed by cyclophosphamide mobilization effectively decreases the incidence of engraftment syndrome in patients with POEMS syndrome who undergo stem cell transplantation

Abstract: High‐dose chemotherapy with autologous stem cell transplantation (ASCT) can achieve excellent clinical responses in patients with POEMS syndrome (Jimenez Zepeda et al., Blood 2010;116:2403; Gertz et al., Am J Hematol 2005;79:319–328; Gherardi et al., Ann Neurol 1994;35:501–505; Gattinoni et al., Nat Rev Immunol 2006;6:383–393; Salem et al., J Immunol 2009;182:2030–2040; Salem et al., Cancer Immunol Immunother 2010;59:341–353; Salem et al., Cell Immunol 2010;261:134–143). However, High‐dose melphalan with ASCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome. 1 In addition, Jimenez-Zepeda et al 18 reported that short-term induction therapy of CY and prednisone before transplantation could significantly decrease the incidence of engraftment syndrome and reduce transplant-related mortality. Therefore, pretreatment with high dose of CY might decrease the level of pro-inflammatory cytokines, relieve disease activity and reduce G-CSF-related adverse effects, which might improve the efficacy and safety of mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome. 1 In addition, Jimenez-Zepeda et al 18 reported that short-term induction therapy of CY and prednisone before transplantation could significantly decrease the incidence of engraftment syndrome and reduce transplant-related mortality. Therefore, pretreatment with high dose of CY might decrease the level of pro-inflammatory cytokines, relieve disease activity and reduce G-CSF-related adverse effects, which might improve the efficacy and safety of mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies on PES have come to the following conclusions: (1) common occurrence after UCBT, (2) development before neutrophil recovery, (3) associations with: cyclosporine in GVHD prophylaxis and total body irradiation in conditioning therapy, (4) enhancement of engraftment without significant morbidity as well as early achievement of complete donor chimerism, and (5) controversial association with development of acute GVHD [20,[36][37][38]. -Skin rash -Pulmonary infiltrates -Diarrhea commencing 24 hours before or at any time after the first appearance of neutrophils (1) GVHD prophylaxis using methotrexate in UCBT, (2) use of cyclophosphamide and prednisolone in induction followed by cyclophosphamide mobilization in patients with POEM syndrome, (3) use of donor lymphocyte infusions in relapsed CML after allogeneic HSCT, and (4) steroid prophylaxis significantly decreases the risk of ES following autologous HSCT and is associated with shortened hospitalization without increasing the risk of infection [42][43][44][45].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…2 There have been multiple reports of high-dose chemotherapy with peripheral blood stem cell transplantation in patients with POEMS, but most studies are small and long-term outcomes are not well delineated. [3][4][5][6][7][8][9][10][11][12][13] Since 1999, we have expanded our experience with the use of autologous stem cell transplantation (ASCT) in patients with POEMS syndrome. In this article, we report the long-term outcomes of our cohort of POEMS patients treated with ASCT with an emphasis on identifying factors that were significantly associated with a risk of progression or relapse of POEMS syndrome after peripheral blood stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%